CULTURAL ASPECT OF ETHNOLINGUISTICS - Барчук, В. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article the correlation of cultural linguistics and ethnolinguistics is established, the cultural meanings of the ethnic language units are outstanding as well. The theoretical research bases of the cultural language features of ethnos is defined, and roles of mythological unit, symbol, concept, meme in the process of formation of the lingual personality are characterized.